Endophytic Bacteria Research in Indonesia: A Review - Dwi Hartanti; Risda Yunita (Program Studi Farmasi FMIPA Universitas Lambung Mangkurat, 2016)
ABSTRACTIn this review, a considerable amount of works that have been published on the endophytic bacteria isolated from host plants collected in Indonesia is reported. The objective of this review is to give an overview of the reported studies from the selection of host plants, the isolated bacteria, and the screened bioactivity of endophytic bacteria derived from Indonesian host plants.Keywords: bioactivity, endophytic bacteria, host plant, Indonesia. ABSTRAK Review ini membahas tentang data-data terkait bakteri endofit yang diisolasi dari tumbuhan inang yang tumbuh di Indonesia. Tujuan dari review ini adalah untuk memberikan gambaran secara detail tentang seleksi tumbuhan inang, bakteri yang berhasil diisolasi dan juga bioaktivitas yang diuji dari bakteri endofit yang berhasil diisolasi tersebut.Kata kunci: bakteri endofit, bioaktivitas, Indonesia, tumbuhan inang.